PENGARUH KUALITAS LAYANAN ELEKTRONIK PADA LOYALITAS ELEKTRONIK (KEPUASAN ELEKTRONIK SEBAGAI VARIABEL MEDIASI DAN KEPERCAYAAN YANG DIRASAKAN SEBAGAI VARIABEL MODERASI) - Utami, Wiry (MENARA EKONOMI, 2017)
This research examine the influence of electronic service quality that consist of fourdimensions are efficiency, system availability, fulfillment and privacy on electronic loyalty, withelectronic satisfaction as mediating variable, perceived trust as moderating variables. Datafor this research were collected by offline and online survey and administered to 237 respondents.The hypothesis testing was conducted using multiple regression analysis, simple regressionanalysis, hierarchical regression analysis.Findings of this study indicate that efficiency, system availability, fulfillment of electronicservice quality are strongest predictors of electronic satisfaction, whereas privacy has no positiveinfluence on electronic satisfaction. This study confirms that electronic satisfaction has stronginfluence on electronic loyalty. Electronic satisfaction also partially mediation the positiveinfluence of efficiency and fulfillment on electronic loyalty. This study reveals that perceived trusthas no moderating role in the influence of electronic satisfaction on electronic loyalty.Keywords : online shopping, electronic service quality, perceived trust, electronic satisfactionand electronic loyalty